Komunikasi Pemasaran Songadventure Pada Masa COVID-19 - Kusuma Jaya, I Nyoman Prima; Farida; Widya Desary Setia Wardhani (Journal Communication Specialist, 2023)
ABSTRACT Marketing communications during the Covid 19 pandemic are currently very diverse and are widely used by tourism managers for promotional or marketing needs and also branding to expand marketing reach, this research was conducted to find out how songadventure marketing communications are during the Covid 19 pandemic. There are many ways to carry out promotions or marketing during the Covid 19 pandemic, one of which is to use the internet and social media as a medium for carrying out marketing communications to convey promotions or products that you want to convey to the public with a very wide reach. This study used a qualitative method, with data collection techniques in the form of observation, in-depth interviews, documentation, and literature study. From the results of this study, it can be concluded that in Songadventure marketing communications during the Covid 19 pandemic it was more about maximizing the use of the internet and social media as a means of marketing or product promotion that you want to offer and also as a medium for information to the public with a very wide reach. spacious and cheap. ABSTRAK Komunikasi pemasaran pada masa pandemic covid 19 pada saat ini sangat beragam dan banyak sekali digunakan oleh pengelola pariwisata untuk kebutuhan promosi ataupun pemasaran dan juga branding untuk memperluas jangakuan pemasaran, penelitian ini dilakukan untuk mengetahui bagaimana komunikasi pemasaran songadventure pada masa pandemic covid 19. Banyak sekali cara untuk melakukan promosi atau pemasaran pada masa pandemic covid 19, salah satunya ialah memanfaatkan internet dan media social sebagai salah satu media untuk melakukan komunikasi pemasaran untuk menyampaikan promosi atau produk yang ingin di sampaikan kepada masyarakat dengan jangkauan yang sangat luas. Penelitian ini menggunakan metode kualitatif, dengan Teknik pengumpulan data berupa observasi, wawancara mendalam, dokumentasi, dan studi pustaka. Dari hasil penelitian ini dapat disimpulkan bahwa dalam komunikasi pemasaran songadventure pada masa pandemic covid 19 lebih kepada memamksimalkan penggunaan internet dan media social sebagai salah satu sarana pemasaran atau promosi produk yang ingin di tawarkan dan juga sebagai salah satu media untuk informasi kepada masyarakat dengan jangkauan yang sangat luas dan murah.